Assessment of the impact of irrigation with low-quality mine water on virgin and rehabilitated soils in the Upper Olifants Basin - Idowu, O.A.; Lorentz, S.A.; Annandale, J.G.; McCartney, Matthew P.; Jovanovic, N.Z. (2008)
Low-quality mine water from collieries may be used in large quantities to irrigate agricultural crops on virgin (unmined) and rehabilitated soils in South Africa. Such a use could enhance crop production and allow environmentally sustainable mine water disposal. In this study, the volume and qualities of the runoff from two centre pivots irrigated with moderately saline mine water, as well as their soil water salinities, were monitored and used to determine water and salt balances, using the modified ACRU agrohydrological model, ACRU2000, and its salinity module, ACRUSalinity. At both sites, much of the water evaporated, while a significant part of the salt input either recipitated or remained with the water in the soil horizons. A higher percentage of drainage water (and salinity) were retained as ground water storage and a lower percentage of runoff occurred in the rehabilitated sandy loam soil, while a higher percentage of salts accompanied runoff in the virgin clayey soils. Simulated salt saturation values indicate that many crops could be successfully irrigated at 100% yield potential at either site. Electrical resistivity surveys were carried out at both sites. A general decrease in resistivities with depth in both the virgin and rehabilitated soils reflected the decreasing influence of the mine water used for irrigation with depth and the precipitation of salts in the soils close to the ground surface. The occurrence of a thicker, low- resistivity, near-surface layer near the exit of each pivot area indicates that the water and salt content of the subsurface increased in the direction that the surface and near-surface irrigation water flowed.